2003
DOI: 10.1172/jci200317295
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of p38 MAPK promotes hypertrophic cardiomyopathy through upregulation of calcineurin-NFAT signaling

Abstract: The MAPKs are important transducers of growth and stress stimuli in virtually all eukaryotic cell types. In the mammalian heart, MAPK signaling pathways have been hypothesized to regulate myocyte growth in response to developmental signals or physiologic and pathologic stimuli. Here we generated cardiac-specific transgenic mice expressing dominant-negative mutants of p38α, MKK3, or MKK6. Remarkably, attenuation of cardiac p38 activity produced a progressive growth response and myopathy in the heart that correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(48 citation statements)
references
References 45 publications
6
42
0
Order By: Relevance
“…PKCε was confirmed to activate an AP-1.luc reporter construct in these cells. Furthermore, potentiation of CN-dependent activation of an NFAT.luc reporter by PKCε suggests that mechanisms independent of AP-1 may also operate, such as direct posttranslational modification of NFAT itself (68,69). Both LPS and AngII activated pGL3.rCOX2.luc and NFAT.luc reporters as expected.…”
Section: Discussionsupporting
confidence: 60%
“…PKCε was confirmed to activate an AP-1.luc reporter construct in these cells. Furthermore, potentiation of CN-dependent activation of an NFAT.luc reporter by PKCε suggests that mechanisms independent of AP-1 may also operate, such as direct posttranslational modification of NFAT itself (68,69). Both LPS and AngII activated pGL3.rCOX2.luc and NFAT.luc reporters as expected.…”
Section: Discussionsupporting
confidence: 60%
“…In another study, 8-10 week old heterozygous p38a and p38b mice were used. In contrast to p38b mice, but similar to the former study, p38a mice showed an increased survival and resistance to myocardial infarction with no further abnormalities in body and heart weight, heart architecture, dia-and systolic blood pressure and LV pressures Braz et al 2003). The role of p38a in hypertrophy and fibrosis as a response to cardiac ischemia was addressed by construction of cardiac-specific p38a D40-83 floxed mice in C57BL/6 background.…”
Section: Jnk3supporting
confidence: 58%
“…Additionally, some researchers noted defects in T-cell function and cytokine production Kaiser et al 2004). Cardiac-specific TG mice expressing dnMEK3 displayed enhanced cardiac hypertrophy following aortic banding, angiotensin II infusion and phenilephrine infusion for 14 days (Braz et al 2003).…”
Section: Mek3mentioning
confidence: 99%
See 1 more Smart Citation
“…At cellular and molecular levels, cardiac hypertrophy is characterized by increased myocyte size, sarcomerogenesis, and reexpression of a set of fetal genes, such as the atrial natriuretic factor, B-type natriuretic peptide, and ␤-myosin heavy chain genes, which are coordinately controlled by a subset of hypertrophy-responsive transcription factors, including myocyte enhancer factor 2 (MEF2), nuclear factor of activated T cells (NFAT), and GATA4 (2, 3) (4). Depending on the upstream hypertrophic stimuli, these transcriptional regulators can be directly phosphorylated or dephosphorylated by protein kinases, such as mitogen-activated protein (MAP) kinase and protein kinases A and C, as well as the calcium-activated phosphatase calcineurin, to facilitate hypertrophic gene expression (5)(6)(7)(8)(9). Disruption and/or attenuation of the activities of these transcription factors could serve as a potential therapeutic approach in terms of inhibiting the hypertrophic responses in the heart (10)(11)(12).…”
mentioning
confidence: 99%